Segregação imposta no contexto da dinâmica sócio-espacial da cidade de Vitória (ES) : o caso de mangue seco-Andorinhas - Rezende, Aldo (2012)
From Mangue Seco-Swallows, the socio-spatial segregation imposed is the subject of this research, enforcement in the context of critical reading in proceedings related to the selective and unequal forms of ownership, production, modeling and use of urban space here referenced as a system of interchangeable objects and actions dialectically related. Accordingly, with emphasis on specific aspects related to the historical process of growth and urbanization of the city of Victoria, will seek through studies and analyzes of the genesis of a place called Mangue Seco-Swallows, highlight the historical aspects of the stages of consolidation of the place considered provided subnormal settlement and precarious, thereby, from the urban-housing interventions promoted by local authorities, through the Earth Project (1998-2004), recognize the key attributes of the phenomenon of segregation today.